Surgical Management of Falcotentorial Junction Tumors: A Case Series Report - Liu, Peixi; Wang, Xiaowen; Liu, Yingjun; Cai, Jiajun; Yang, Zixiao; Quan, Kai; Zhu, Wei; Song, Jianping (Frontiers in Oncology, 2022)
Objective: The surgical strategy for falcotentorial junction tumours remains complex. Different approaches are selected according to the location and growth pattern of the tumour and the operator's experience. This report reviews our single-institution experience in the surgical management of falcotentorial junction tumours. Methods: We retrospectively reviewed the clinical and imaging data, surgical strategy, and follow-up outcomes of 49 patients treated from 2007 to 2020. Result: All 49 patients (12 male, 37 female, mean age 56.3±11.3 years) underwent safe tumour resection. The most common complaints were headache (43%), dizziness (39%), and unstable gait (16%). Thirty percent of the tumours showed calcification, and computed tomography scans revealed hydrocephalus in 36% of the patients. On magnetic resonance imaging, 43% of the tumours were unilateral. According to the Asari classification, the tumours were divided into inferior (16%), superior (29%), anterior (22%), and posterior types (33%). The occipital interhemispheric approach (88%) and supracerebellar-infratentorial approach (10%) were primarily used to reach the tumours. Pathology revealed that 85.7% of the tumours were meningioma and 14.3% were hemangiopericytoma. Of the 49 patients, 15 achieved a Simpson grade I resection, and 29 achieved a Simpson grade II resection. The follow-up rate was 77.6% (38/45); 94.7% of patients (36/38) achieved a favourable outcome, and 9 experienced tumour recurrences. Conclusion: Surgical approach selection depends on the growth characteristics of the tumour and the degree of venous or sinus involvement. The occipital interhemispheric approach is the most commonly used and safest approach for falcotentorial junction tumours with multiple brain pressure control assistance techniques.